The impacts of resilience on the association between illness uncertainty and sleep quality among patients with type 2 diabetes mellitus - Xin-Ge Wang; Yu-Qiong Wen; Hui-Bing Kuang; Li-Xia Lin; Hong Cui (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective was to investigate the relationship between resilience, illness uncertainty, and sleep quality in patients with type 2 diabetes mellitus (T2DM). Methods: This cross-sectional study was conducted from September 2019 to August 2020 from a tertiary hospital in Guangzhou, China. Totally, 205 participants completed questionnaires concerning demographic characteristics, Pittsburgh sleep quality index, Mishel uncertainty in illness scale (MUIS), and Connor-Davidson Resilience Scale (CD-RISR) were collected by convenience sampling. Multiple hierarchical regression analysis was used to evaluate the interaction of illness uncertainty, resilience, and sleep quality. The mediating role of resilience was also tested. Results: The total score of illness uncertainty was 94.68 ± 11.19 in T2DM patients, which was proved in the medium level. There was a significant negative correlation between the total CD-RISR score and total MUIS score (r = −0.716, P < 0.01); there was a significant negative correlation between the total CD-RISR score and total PISQ score (r = −0.806, P < 0.01); total MUIS score was positively correlated with PISQ score (r = 0.872, P < 0.01). Psychological resilience could partially mediate the association between sleep quality and the level of illness uncertainty, and the mediating effect was 0.293, accounting for 34.20% of the total effect. Conclusion: Patients with T2DM have a moderate level of illness uncertainty, and it was negatively correlated with mental resilience level and positively associated with sleep quality. Medical staff should strengthen psychological intervention for T2DM patients to reduce the sense of uncertainty.